Relationship between Social Media Marketing and Brand Loyalty with Moderating Effect of Culture: An Evidence from University Students - Nabi, Dr. Ghulam; Shah, Dr. Nazir Haider; Shaheen, Dr. Muhammad Naqeeb ul Khalil; Zeb, Naveeda; Hussain, Mr. Abrar (The journal of contemporary issues in business and government, 2021)
This research aimed to determine the relationship between social media marketing and brand loyalty. It also explores the moderating role of culture in the relationship between social media marketing and brand loyalty. 177 students from the universities of Pakistan and Azad Jammu and Kashmir were selected as a sample for conducting a cross-sectional survey. Self-managed questionnaires were used for data collection and correlation and regression analyses were used to analyze the data. The research results showed a positive impact of social media marketing on brand loyalty. Moreover, culture can alleviate the relationship between social media marketing and brand loyalty, which showed that culture had an impact on the use of social media and brand loyalty. The current study will be helpful for the marketers and decision-makers of the brands to make important decisions to increase Brand Loyalty by using Social Media Marketing but keeping in mind the cultural aspects.